2015
DOI: 10.1586/14737175.2015.1036743
|View full text |Cite
|
Sign up to set email alerts
|

Nano-ropinirole for the management of Parkinsonism: blood–brain pharmacokinetics and carrier localization

Abstract: Finally, the investigation demonstrated that intranasal delivery of mucoadhesive nanocarrier might play as a potential candidate in the management of Parkinson's disease and related brain disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…In what concerns the oral and oromucosal routes, the limitations are related with altered physiological states of individuals (such as nausea and vomiting, or the hypersalivation and inability to swallow that happen during an epileptic seizure) [3,4,[9][10][11], large intersubject absorption rate variability, slow onset of action, drug-drug and drug-food interactions and cytochrome P450 induction [8,10,[12][13][14][15][16][17]. Moreover, IN delivery offers the possibility of avoiding hepatic first pass metabolism and can reduce drug distribution to non-targeted sites, thereby minimizing systemic adverse effects [8,[18][19][20][21][22][23][24].…”
Section: Fig 1 Schematic Representation Of Intranasal (In) Deliverymentioning
confidence: 99%
“…In what concerns the oral and oromucosal routes, the limitations are related with altered physiological states of individuals (such as nausea and vomiting, or the hypersalivation and inability to swallow that happen during an epileptic seizure) [3,4,[9][10][11], large intersubject absorption rate variability, slow onset of action, drug-drug and drug-food interactions and cytochrome P450 induction [8,10,[12][13][14][15][16][17]. Moreover, IN delivery offers the possibility of avoiding hepatic first pass metabolism and can reduce drug distribution to non-targeted sites, thereby minimizing systemic adverse effects [8,[18][19][20][21][22][23][24].…”
Section: Fig 1 Schematic Representation Of Intranasal (In) Deliverymentioning
confidence: 99%
“…Several studies have reported that the intranasal route can be a good option as a nose to brain targeting approach for treating the depressive disorders. , Trigeminal and olfactory pathways have been considered to be merely the routes via which the brain is linked to the outside environment [ , ]. Drugs with limited oral bioavailability because of substantial metabolism have been studied using this route as a viable alternative. Additionally, the utilization of this nasal route of administration of medication allows the various therapeutics to avoid the first-pass effect. So, intranasal doses are frequently considered to be 2 to 10 times lower than doses that are administered orally .…”
Section: Discussionmentioning
confidence: 99%
“…The qualitative localization of florescent labelled PLGA NPs was determined in brain tissues by confocal laser microscopy (Olympus Fluoview™, Melville, NY, USA) [ 25 , 26 ]. For preparation of DAPI (4-6-diamidino-2-phenylindole) loaded PLGA nanoparticles, 0.2 mL of DAPI solution (50 μ g/mL in ethanol) was dissolved in PLGA solution and nanoparticles were prepared in similar way as described earlier.…”
Section: Methodsmentioning
confidence: 99%